The neo-colonized entity: Examining the ongoing significance of colonialism on free speech in Singapore. Issue 2 (2nd July 2020) - Thanapal, Sangeetha
ABSTRACT: This paper examines the use of colonial era laws to restrict free speech in Singapore, along with more recent laws that are meant to stifle criticism of the state. It draws a link between current statutes and colonial laws, showing that two of the fundamental decrees restricting free speech in Singapore originated from British colonialism. It concludes by pointing out that free speech does exist in Singapore in some respects, in that it remains the sole purview of the state which exercises free speech liberally but uses the Singaporean justice system to deny the same for its citizens.